2012
DOI: 10.1103/physrevb.85.245204
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale structure and band-gap bowing in Cu(In,Ga)Se2

Abstract: Mixed systems such as the Cu(In,Ga)Se 2 chalcopyrite semiconductor consist of different local atomic arrangements, that is, of different combinations of first-nearest-neighbor cations surrounding the Se anions. The anion position of Cu-III-VI 2 compounds is predicted to strongly influence the material band gap. We therefore used extended x-ray absorption fine structure spectroscopy to study the atomic-scale structure of Cu(In,Ga)Se 2 as a function of composition. Based on these results, the anion position was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 34 publications
(65 reference statements)
10
67
0
Order By: Relevance
“…EX-AFS measurements of both CIGS and CIGSe have shown that the element-specific bond lengths are nearly constant over the whole compositional range despite the change in lattice constants. 5,12 This behavior closely resembles the findings for other mixed semiconductor systems as first reported for (In,Ga)As 27 and later confirmed for many other III-V and II-VI ternary compounds.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…EX-AFS measurements of both CIGS and CIGSe have shown that the element-specific bond lengths are nearly constant over the whole compositional range despite the change in lattice constants. 5,12 This behavior closely resembles the findings for other mixed semiconductor systems as first reported for (In,Ga)As 27 and later confirmed for many other III-V and II-VI ternary compounds.…”
Section: Discussionsupporting
confidence: 75%
“…This means that although the band gap and thus the energy of the conduction band minimum changes, only the anion absorption edges exhibit a corresponding shift supplying relevant macroscopic electronic information whereas the cation absorption edges remain unchanged. X-ray absorption measurements of CuIn x Ga 1−x Se 2 (0 ≤ x ≤ 1) also show no appreciable shift in the Cu, Ga and In K-edge positions 5 suggesting that these findings represent general features of material systems with different cation species such as, but not limited to, chalcopyrites. Note that a similar behaviour was in fact observed in the completely different context of the investigation of magnetism and insulator/metal transitions as a function of doping for Sr doped cobaltites (La 1−x Sr x CoO 3 ).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The temperature dependence of the detrapping effect can be developed into a method to characterise the trap states themselves [95]. Besides affecting the doping density and the recombination behaviour, the electronic band structure is influenced by the details of the atomic structure: while the average bond lengths in Cu(In,Ga)Se 2 follow a linear Vegard's law, it was found by X-ray absorption measurements, that the In-Se and Ga-Se bond lengths remain essentially constant throughout the whole composition range between CuInSe 2 and CuGaSe 2 [96]. This leads to a non-linear displacement of the anions, which contributes to the bowing behaviour of the band gap.…”
Section: à3mentioning
confidence: 99%